(untitled) - Alexander, W.L.; Plummer, A.; Spence, H. D. M. (ed.) (Grand Rapids, 1950)
.AB: Hervey, H.C.
Vol.3 - Deuteronomy, xliii,586p., Vol.3 - Joshua, xxxviii,381p., Vol.3 - Judges, viii,218p.
Keywords: Bible-commentaries; Spence, H. D. M. (ed.); Exell, Joseph S. (ed.); Plummer, A